Vocational Education: A Mean to Educate and Empower the Socio-economic Status of Marginalised Communities - Gandhi, E. Arumuga (JOURNAL OF INDIAN EDUCATION, 2011)
From the days of the Wood’s Despatch there has been loud cry for the introduction of vocational education as the solution to the educational problems of the country, endorsed subsequently by several Commissions and Committees of both British and Independent India. The national leaders of India such as Mahatma Gandhi had supported it to be introduced in school education. Through diversification and by tracking the students in higher secondary vocational stream, it was believed that many educational problems could be solved. Vocational education is concerned with providing facilities for a sizeable section of students for whom bread-winning is far more important than the pursuit of higher education: And to prevent an unhealthy influx into higher education, it is essential to evolve a system of education and training quite apart from general education, which aims to prepare the students for prospective vocations. Treating and offering vocational education through a separated vocational stream of education as offered at higher secondary stage would best do this preparation. Hence, it is the felt need to evaluate that to whom the vocational education has been benefitted as conceptualised and proposed. The present paper discusses the generalisations derived through the study.